2007
DOI: 10.1345/aph.1h395
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Effect of Oral Rifaximin on the Pharmacokinetics of Ethinyl Estradiol/Norgestimate in Healthy Females

Abstract: Administration of a 3 day dosing regimen of oral rifaximin was well tolerated and did not alter the pharmacokinetics of a commonly used combination OC containing EE and norgestimate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
0
24
0
2
Order By: Relevance
“…Previous studies revealed CYP3A4 induction by RIFax in a human hepatocyte model. Two clinical studies that used MDZ and an oral contraceptive containing ethinyl estradiol and norgestimate (Trapnell et al, 2007) demonstrated that RIFax did not alter the pharmacokinetics of these drugs, indicating that RIFax had no significant effect on intestinal or hepatic CYP3A4 (http://www.salix.com/). However, in the current study, intestinal CYP3A11 was significantly up-regulated in hPXR mice treated with RIFax.…”
Section: Rifaximin Is a Gut-specific Human Pxr Activator 395mentioning
confidence: 99%
“…Previous studies revealed CYP3A4 induction by RIFax in a human hepatocyte model. Two clinical studies that used MDZ and an oral contraceptive containing ethinyl estradiol and norgestimate (Trapnell et al, 2007) demonstrated that RIFax did not alter the pharmacokinetics of these drugs, indicating that RIFax had no significant effect on intestinal or hepatic CYP3A4 (http://www.salix.com/). However, in the current study, intestinal CYP3A11 was significantly up-regulated in hPXR mice treated with RIFax.…”
Section: Rifaximin Is a Gut-specific Human Pxr Activator 395mentioning
confidence: 99%
“…An example is a recent study of rifaximin. 3 This is a rifamycin similar to rifampicin, but less than 1 per cent of a dose is absorbed orally and it is used for gastrointestinal infections. Because of its poor absorption, it would not be expected to induce the metabolism of ethinyloestradiol, as does rifampicin.…”
Section: Pharmacokinetic Interaction Studiesmentioning
confidence: 99%
“…Rifaximin is used in the treatment of irritable bowel syndrome and is structurally similar to other rifamycins. Not surprisingly, rifaximin is a PXR activator in vitro but uncharacteristically, it does not cause inductive drug interactions as was demonstrated in the absence of effect on either ethinylestradiol or midazolam pharmacokinetics Trapnell et al, 2007). Here, the lack of in vivo inductive effect is related to the fact that rifaximin is not absorbed to any great extent into the systemic circulation to cause an elevation of hepatic drug elimination .…”
Section: Drugs and Herbal Medicines Involved In Clinically Relevantmentioning
confidence: 82%